Fostering the Environmental Performance of Hotels in Pakistan: A Moderated Mediation Approach From the Perspective of Corporate Social Responsibility - Ahmed, Bilal; Xie, Hongming; Zia-Ud-Din, Malik; Zaheer, Muhammad; Ahmad, Naveed; Guo, Manman (Frontiers in Psychology, 2022)
The Islamic Republic of Pakistan has been a mere victim of climate change in recent years. The country needs emergency measures at every level to mitigate environmental dilapidation. The role of enterprises in the country’s environmental efforts is critical. In this regard, the hotel sector is known for its outsized carbon footprint. Knowing this, the current study aims to improve a hotel enterprise’s environmental performance (ENP) as an outcome of corporate social responsibility (CSR). The study also considers the mediating role of pro-environmental behavior (PEB) of employees and the moderating role of altruistic values (ALT). A hypothesized model was developed, which was validated by employing the structural equation modeling technique. The empirical results confirmed that CSR, directly and indirectly (through PEB), positively induces the ENP of a hotel enterprise. Whereas the conditional indirect role of ALT was also found significant. The study offers different implications for theory and practice, among which one important takeaway for the hotel sector is to realize the importance of employees to spur ENP of a hotel enterprise through their eco-friendly behavior. At the same time, the current work also advances the theory by highlighting the moderating role of ALT between the indirect relationship of CSR and ENP.